Pension reforms in Poland and elsewhere: The view from Paris - Peter Jarrett (Center for Social and Economic Research (CASE), 2011)
Recently several countries, including Estonia, Latvia, Lithuania, Hungary, Poland, Romania and Slovakia, have at least partially reversed their earlier moves towards compulsory defined-contribution schemes. This paper concentrates on Poland, which just reduced contributions going to the mandatory second pillar from 7.3 to 2.3% of earnings with that amount diverted to the public pension regime (ZUS). Trying to solve the problem of public finance sustainability by radically shrinking the second tier of the pension system has obvious costs in terms of poverty among old-age pensioners. Their incomes will fall sharply relative to those of working-age population. Partially reversing pension reform will also cost Poland in terms of risk spreading and capital market development. It will also undermine the population's trust in the system. There is no alternative for achieving public finance sustainability but to restrain current spending and/or raise taxes. The pensionable age should be raised further (probably to 70 by mid-century), even in the general scheme, to deal with the long-run demographic challenge and be equalized across the two sexes. The authorities should move to unify pension provision systems, in particular by phasing out the farmers' regime (KRUS) and making pensions for miners and others with special regimes closer to actuarially neutral.
Keywords: G23; H55; J26; 330; pension system; pension reform; pension adequacy; pension funds; retirement age; replacement age; Poland; Altersvorsorge; Rentenreform; Armut; Polen; OECD-Staaten